Eurasian Economic Union: investment climate and FDI overview (Journal of Economic Research & Business Administration, 2016)
The article examined the investment climate of Eurasian economic union (EEU) countries and dynamics of foreign direct investment (FDI) flows in the region. Most theoretical and empirical studies refer to the positive impact of integration on economic performance, trade and foreign direct investment. The FDI flows to the Eurasian economic union members follow an increasing tendency, with an exception for Russia, which experiences a downturn in FDI inflows from the European countries. In the intraregional aspect, Kazakhstan obtained more FDI since the adoption of Customs union, which partially verifies the positive impact of intraregional cooperation and liberalizing reforms on FDI. The investment climate characteristics are relatively satisfactory for all three countries; however, some institutional reforms are required for more favorable conditions of establishing a foreign firm, additionally the allowed shares of foreign ownership in such sectors as: media, telecommunication, insurance, transportation and electricity can be increased for expanding investment opportunities in the EEU region.
Keywords: Eurasian economic union; FDI (foreign direct investment); investment climate.